Pickup ion measurements by MAVEN: A diagnostic of photochemical oxygen escape from Mars. Issue 14 (21st July 2014) - Rahmati, A.; Cravens, T. E.; Nagy, A. F.; Fox, J. L.; Bougher, S. W.; Lillis, R. J.; Ledvina, S. A.; Larson, D. E.; Dunn, P.; Croxell, J. A.
Abstract A key process populating the oxygen exosphere at Mars is the dissociative recombination of ionospheric O2+, which produces fast oxygen atoms, some of which have speeds exceeding the escape speed and thus contribute to atmospheric loss. Theoretical studies of this escape process have been carried out and predictions made of the loss rate; however, directly measuring the escaping neutral oxygen is difficult but essential. This paper describes how energetic pickup ion measurements to be made near Mars by the SEP (Solar Energetic Particle) instrument on board the MAVEN (Mars Atmosphere and Volatile EvolutioN) spacecraft can be used to constrain models of photochemical oxygen escape. In certain solar wind conditions, neutral oxygen atoms in the distant Martian exosphere that are ionized and picked up by the solar wind can reach energies high enough to be detected near Mars by SEP.